Estrategias locales de desarrollo sostenible de bajas emisiones en zonas rurales: Informe de actividades en la Sierra Central del Perú - Olivares, E.; Ccanto, R.; Nuñez, E.; Mendoza, J.; Fonseca, C.; Pradel, W. (International Potato Center, 2023)
The implementation of activities in 2023 is focused on integrated emissions reduction and sustainability, as well as promoting investments in value chains oriented towards national and regional objectives of adaptation and mitigation of climate change, poverty, social inclusion and biodiversity. In this sense, the strategy is framed in three results: i) Strengthening Regional Climate Change Platforms, ii) Strengthening organizational, productive and commercial capacities with an agroecological approach, and iii) Promotion of innovations in resilient value chains with low emissions of GHG. The Regional Climate Change Strategy (ERCC for its Spanish Acronyms) is the comprehensive climate change management instrument that guides and facilitates State action at the regional level; and is aligned with the National Climate Change Strategy, and includes action plans and contributes to the implementation of the NDCs, without moving away from the regional reality itself. Its preparation is done in accordance with the guidelines prepared by the National Climate Change Authority (MINAM). The Yanapai Group is a member of the Regional Climate Change Council of Junín, whose functions include updating the ERCC. The Guinean pig producer association is made up by young entrepreneurial women, many of them have experience in family raising guinea pigs, others with little experience and some have no experience. They look at this guinea pig production chain as an activity that can generate income without leaving their community and at the same time take care of their children. The process of forming the members of the association was voluntary and was carried out in the first half of the year. 2023, with participation in the induction workshop for organizations and bidders held on May 10, 2023. On May 19, the president, representing the members of the association, signed the agreement. With the AgriLAC Resilient Initiative, the women's organization was strengthened, achieving the formation of a cooperative. Guian pig association members are eager to learn and develop skills in raising guinea pigs and strengthen their organizational capacity to improve their income and provide better living conditions for their young children and the members of their family. home; and develop their leadership capacity and commitment to their community. The baseline, diagnosis and initial home visits allow us to obtain real and timely information about the situation "before" starting the Implementation Plan; and adequately project its development, generating objective, reliable and sufficient qualitative and quantitative data to measure changes and adjust the goals and/or expected results and intervention strategies. The exchange workshop helped us identify topics to investigate and also to implement, such as technical irrigation + bioinputs (compound fertilizers – biopesticides) + quality seeds, and extend pastures/rests to larger areas and neighboring communities, as well as the need of more evidence on different pasture establishment strategies (guano, seed density) across diverse agroecosystems, especially on poorer soils.